PENGARUH DANA PIHAK KETIGA TERHADAP LABA BERSIH PT BANK BCA DIGITAL (BLU) PERIODE 2022-2024 - Sabella, Maria Emily; Pandjaitan, Shilo Hasiholan; Manurung, Elizabeth Tiur (Komunitas Manajemen Kompetitif, 2025)
This study aims to measure the impact of Third Party Funds components, namely demand deposits, savings, and time deposits, on the Net Profit of PT Bank Digital BCA (Blu) for the period January 2022 to December 2024. Using a quantitative approach, monthly time series data were processed using multiple linear regression. The independent variables consist of the values of demand deposits, savings, and time deposits; the dependent variable is Blu's Net Profit. The regression model was tested through classical assumptions: linearity, normality of residuals, homoscedasticity, independence of residuals (no autocorrelation), and non-multicollinearity (with Variance Inflation Factor and condition number). The results of the analysis show that savings have a positive and significant effect on net profit (β = 0.0378; p < 0.01), while time deposits have a negative significant effect (β = -0.01286; p < 0.05). The demand deposit variable does not provide a significant contribution to the model. Keywords: Third Party Fund, Demand Deposit, Saving, Time Deposit, Net Profit.